Preparation method and application of ultrahigh nickel ternary positive electrode material coated with niobium and tungsten composite doped ZIFs derivative
By using niobium and tungsten composite doped ZIFs derivative coating technology in ultra-high nickel ternary cathode materials, the problem of material structural instability and performance degradation is solved, and the effect of significantly improving rate performance and cycling performance is achieved.
Patent Information
- Application Number
- CN202411674071.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-29
AI Technical Summary
The existing ultra-high nickel ternary cathode materials have problems of structural instability and performance degradation, especially in the case of high nickel content, Ni ion migration leads to structural transformation, affecting battery performance and safety.
The ultra-high nickel ternary positive electrode material preparation method coated with niobium and tungsten composite doped ZIFs derivatives is used to synthesize and coat the ultra-high nickel ternary precursors doped by co-precipitation and high-temperature firing, and further enhance the conductivity and stability of the material through the coating of the ZIFs derivatives.
It significantly improves the rate performance and cycling performance of the material, inhibits structural degradation, enhances conductivity, reduces the direct contact between the positive electrode material and the electrolyte, and improves the overall performance and safety of the battery.
Smart Images

Figure CN119898826A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ternary lithium-ion battery materials, and in particular to a preparation method and application of an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative composite-doped with niobium and tungsten. Background Art
[0002] With the development of large-scale battery systems such as electric vehicles (EV) and energy storage systems (ESS), higher requirements are placed on the performance indicators of lithium-ion batteries. Therefore, the development of new positive electrode materials with good stability and high specific capacity is the key to further improving the energy density of lithium-ion batteries. As an active positive electrode material, nickel-rich ternary materials have been widely used in commercial lithium-ion batteries due to their good cycle performance, small irreversible capacity loss, and easy synthesis. The general formula is LiNi x Co y Mn 1-x-y O2. NCM ternary cathode materials with different transition metal ratios, such as Ni: Co: Mn = 1:1:1, Ni: Co: Mn = 5:2:3, Ni: Co: Mn = 6:2:2 and Ni: Co: Mn = 8:1:1, have been widely studied. With the increase of Ni content, the energy density of NCM cathode materials is significantly improved. Today, the actual specific capacity of 9-series NCM cathode materials is ≥220 mAh / g, but due to structural instability caused by Ni ion migration, its layered structure is easily transformed into a rock salt structure. In addition, the mixing of Ni / Li cations in the structure and surface cracks of 9-series NCM cathode particles can lead to performance degradation and safety threats.
[0003] In order to solve the problem of structural instability and improve performance, a lot of work has been done on ultra-high nickel ternary positive electrode materials in terms of structural design, coating, doping and cathode particle coating. Cathode doping has been widely used to stabilize the volume and surface structure, thereby improving performance. Commonly used doping elements are Al, Fe, Ti, Y, Nb, W, F and Cl. The bond dissociation energy of Nb-O (753 kJ / mol) is much stronger than that of Ni-O (391.6 kJ / mol), Co-O (368 kJ / mol) and Mn-O (402 kJ / mol). Therefore, the introduction of Nb in NCM materials 5+ It will help to inhibit structural degradation and improve its electrochemical performance. In addition, despite the trace amount of HF in the electrolyte, Nb2O5 remains stable, which reduces the side reactions of the surface electrolyte. The doping of W can effectively inhibit the growth of grains, shorten the transmission distance of lithium ions, and improve the rate performance of the material to a greater extent.
[0004] As a modification method to improve the electrochemical performance of nickel-cobalt-manganese ternary positive electrode material NCM, surface coating is the most common and simplest method, and is therefore widely adopted by the industry. For example, various oxides are used to coat the surface of the NCM material to form a physical protective layer to reduce the side reactions caused by direct contact between the material and the electrolyte. It can also react with the HF produced by the side reactions in the battery to reduce its effect and reduce corrosion on the surface of the material. However, the above-mentioned single-component coating layer has a single function and cannot improve the battery performance of the material more comprehensively. Among them, oxides as insulating materials limit their full play in improving the performance of positive electrode materials. In addition, in common carbon material coating strategies, the carbonized carbon source material needs to be calcined at high temperature under an inert environment. This process is prone to produce reducing substances such as C / CO, which can easily cause lattice oxygen deficiency in the NCM ternary positive electrode material, affect the crystal structure of the material, and then affect the electrochemical activity of the material. Therefore, it is difficult to obtain an ideal carbon-coated NCM cathode material. Summary of the invention
[0005] In view of the problems existing in the background technology, the purpose of the present invention is to provide a preparation method and application of an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] The present invention first provides a method for preparing an ultra-high nickel ternary precursor, comprising the following steps:
[0008] S1. Put soluble nickel salt, cobalt salt and manganese salt into a preparation tank and stir and mix them to obtain a nickel-cobalt-manganese mixed solution, and then put ammonia water and liquid alkali into their corresponding storage tanks respectively.
[0009] S2. In an inert gas atmosphere, turn on the ammonia pump to make the alkalinity of the pure water in the reactor reach the target requirement; then turn on the liquid alkali pump to make the pH of the pure water in the reactor reach the target requirement; then turn on the nickel-cobalt-manganese mixed solution feed pump, and use a continuous method to start a coprecipitation reaction to synthesize an ultra-high nickel ternary precursor. By controlling the feed flow, liquid alkali flow, ammonia flow, pH value, stirring paddle speed, reaction temperature, reaction time and alkalinity, the synthesized ultra-high nickel ternary precursor can reach the required particle size.
[0010] S3. Wash the synthesized ultra-high nickel ternary precursor with water, alkali, dry, sieve and demagnetize to obtain the desired ultra-high nickel ternary precursor.
[0011] Preferably, in S1, the soluble nickel salt is selected from one or two of NiSO4, NiCl2 and NiNO3; the soluble cobalt salt is selected from one or two of CoSO4, CoCl2 and CoNO3; the soluble manganese salt is selected from one or two of MnSO4, MnCl2 and MnNO3.
[0012] Preferably, in S1, the concentration of the aqueous ammonia is 5-15 mol / L, and the concentration of the liquid alkali is 5-15 mol / L.
[0013] Preferably, in S1, the molar ratio of the nickel salt, the cobalt salt and the manganese salt is 90:5:5, 92:3:5, 95:2:3 or 95:3:2.
[0014] Preferably, in S2, the inert gas atmosphere is one of nitrogen, argon and helium.
[0015] Preferably, in S2, the ion concentration in the nickel-cobalt-manganese mixed solution is 85-105 g / L, the feed liquid flow rate of the nickel-cobalt-manganese mixed solution is 15-25 ml / min, the ammonia water flow rate is 3-6 ml / min, and the liquid alkali flow rate is automatically adjusted according to the pH value.
[0016] Preferably, in S2, the pH value in the reactor is 11-13, the speed of the stirring paddle is 500-800 rpm / min, the alkalinity is 0.5-0.7, the reaction temperature is 55-65°C, and the reaction time is 36-72h.
[0017] Preferably, in S2, the particle size range of the ultra-high nickel ternary precursor is 9~11μm.
[0018] Preferably, in S3, the water washing uses pure water or deionized water, the concentration of the liquid alkali used for alkali washing is 1~4 mol / L, the temperature during drying is 100~150°C, the mesh number of the sieve used for screening is 100~500 mesh, and the magnetic field strength of the electromagnetic iron remover used for demagnetization is 1000~6000 Gauss.
[0019] Preferably, the general formula of the ultra-high nickel ternary precursor prepared by S3 is Ni x Co y Mn (1-x-y) (OH)2, where 0.9≤x<1, 0<y<0.1.
[0020] The present invention further provides a method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten, comprising the following steps:
[0021] L1. Grind and mix the ultra-high nickel ternary precursor prepared above with the niobium source to obtain a mixture;
[0022] L2. Add the mixture to the lithium source and mix quickly and evenly in a high-speed pulverizer, then perform the first high-temperature firing in a tubular furnace under an oxygen atmosphere. After the product is ground with an agate mortar, it is sieved and demagnetized in turn to obtain a niobium-doped ultra-high nickel ternary positive electrode material.
[0023] L3. The niobium-doped ultra-high nickel ternary positive electrode material prepared in L2 is quickly mixed with a tungsten source in a high-speed pulverizer, and then fired for a second time at a high temperature in a tubular furnace under an oxygen atmosphere. After grinding with an agate mortar, the materials are sieved and demagnetized in turn to obtain an ultra-high nickel ternary positive electrode material doped with niobium and tungsten.
[0024] L4. The ZIFs material (zeolite imidazolate framework material) was prepared by a room temperature synthesis method, and then sintered in a tubular furnace in a nitrogen atmosphere to obtain a ZIFs derivative.
[0025] L5. Put the ZIFs derivative and the ultra-high nickel ternary positive electrode material doped with niobium and tungsten prepared in L3 into a ball mill for ball milling and mixing to obtain the ultra-high nickel ternary positive electrode material coated with the ZIFs derivative doped with niobium and tungsten.
[0026] Preferably, in L1, the niobium source is at least one of Nb2O5, NbO2, Nb2O3, NbC and NbCl5. The molar ratio of niobium in the niobium source to the molar ratio of all metal elements (i.e. nickel, cobalt and manganese) in the ultra-high nickel ternary precursor is 1:(25-100).
[0027] Preferably, in L2, the lithium source is at least one of LiOH, Li2CO3 and Li2NO3. The molar ratio of the ultra-high nickel ternary precursor to the lithium source is 1:(1.00-1.10).
[0028] Preferably, in L2, the speed of the high-speed pulverizer is 200-500 rpm / min, the pulverization time is 800-1400 s, and the oxygen content in the calcination atmosphere is 95%-99%.
[0029] Preferably, in L2, the conditions for the first high-temperature firing are: continuously introducing oxygen into the tubular furnace, the sintering temperature is 600-900°C, the sintering time is 12-20h, and the heating rate is 2-12°C / min.
[0030] Preferably, in L3, the tungsten source is WO2, WO3, Na2WO4·2H2O, WC and (NH4) 10 W 12 O 41 · At least one of 5H2O. The ratio of the molar number of tungsten in the tungsten source to the molar number of all elements in the ultra-high nickel ternary precursor is 1:(25-100).
[0031] Preferably, in L3, the conditions for the second high-temperature firing are: continuous introduction of oxygen into the tube furnace, sintering temperature of 500-800°C, sintering time of 10-16h, and heating rate of 2-12°C / min. Both the first and second firings are oxidation reactions, which require the participation of oxygen.
[0032] Preferably, in L4, the ZIFs material is one of ZIF-8, ZIF-67, ZIF-11, ZIF-68, and ZIF-71, and the above materials can be prepared or purchased by themselves.
[0033] Preferably, in L4, the sintering conditions for preparing the ZIFs derivatives are: the sintering temperature in the tubular furnace is 500-700°C, the sintering time is 8-12h, and the heating rate is 2-12°C / min.
[0034] Preferably, in L5, the molar ratio of the ZIFs derivative to the ultra-high nickel ternary positive electrode material doped with niobium and tungsten prepared in L3 is 1:(25-100), and the ball milling speed is 200-800 r / min. The ratio of the niobium source and the tungsten source is confirmed to be the best doping ratio through multiple experiments.
[0035] The present invention also provides the use of the niobium and tungsten composite doped ultra-high nickel ternary positive electrode material in lithium ion batteries, including using it as a positive electrode material to prepare a button battery and testing its gram capacity and cycle performance.
[0036] The beneficial effects of the present invention are as follows:
[0037] The ultra-high nickel ternary positive electrode material coated with ZIFs derivatives by niobium and tungsten composite doping has significantly improved rate performance and cycle performance on the basis of the composite doping of niobium and tungsten and coating of ZIFs derivatives. 5+ It will help to inhibit structural degradation and improve its electrochemical performance. Although there is a trace amount of HF in the electrolyte, Nb2O5 remains stable, which reduces the side reactions of the surface electrolyte. Secondly, W doping can effectively inhibit the growth of grains, shorten the transmission distance of lithium ions, and improve the rate performance of the material to a greater extent. Finally, the introduction of ZIFs derivatives enhances the overall conductivity, shortens the transmission distance of lithium ions, and reduces the direct contact between the positive electrode material and the electrolyte. Therefore, the positive electrode material prepared by modification (doping and coating) of the present invention can significantly improve its rate performance and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0039] Figure 1 Flow chart for the preparation of ultra-high nickel ternary positive electrode materials coated with niobium and tungsten composite-doped ZIFs derivatives.
[0040] Figure 2 This is an electron microscope image of the ultra-high nickel ternary positive electrode material coated with the niobium and tungsten composite-doped ZIFs derivative prepared in Example 1.
[0041] Figure 3 The rate performance at different rates of the ultra-high nickel ternary positive electrode material coated with niobium and tungsten composite-doped ZIFs derivatives prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0042] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0043] Figure 1 The figure is a flow chart for preparing ultra-high nickel ternary positive electrode materials coated with ZIFs derivatives doped with niobium and tungsten, and the preparation process of the embodiment conforms to the figure.
[0044] Example 1
[0045] S1: Nickel sulfate, cobalt sulfate and manganese sulfate are prepared into a 100g / L mixed metal solution in a molar ratio of 90:5:5, and then 8mol / L ammonia water and 10mol / L liquid alkali are placed in their corresponding storage tanks. First, the bottom liquid of the reactor is prepared. Under a nitrogen gas atmosphere, the ammonia pump is turned on to make the alkalinity of the pure water in the reactor reach 0.15~0.20mol / L, and then the liquid alkali pump is turned on to make the real pH (40℃) of the pure water in the reactor reach 11.95~12.05. After that, the seed crystal is started, and only the nickel-cobalt-manganese mixed solution feed pump is turned on, with a flow rate of 10~15ml / min, a feed amount of 50~60ml / min, and the real pH (40℃) is reduced to 10.9~11.0. Finally, the growth stage begins, and the coprecipitation reaction is started by the intermittent method. By controlling the flow rate of the feed liquid, the flow rate of the liquid alkali, the flow rate of the ammonia water, the pH value, the speed of the stirring blade, the reaction temperature, the reaction time and the alkalinity, the particle size of the synthesized ultra-high nickel ternary precursor is made to reach 9-10 μm. Finally, the synthesized ultra-high nickel ternary precursor is washed with water, washed with alkali, dried, sieved and demagnetized to obtain the desired ultra-high nickel ternary precursor A1.
[0046] S2: The precursor A1 (20.53 mol) prepared in S1 and Nb2O5 (0.4106 mol) were ground and mixed evenly with an agate mortar, and then LiOH (20.53 mol) was added to the mixed material and quickly mixed evenly in a high-speed pulverizer, and then the first high-temperature sintering was carried out in a tubular furnace under 99% oxygen atmosphere, with a sintering temperature of 650~670℃, a heating rate of 6℃ / min, and a sintering time of 18h. Finally, after grinding with an agate mortar, sieving and demagnetizing, the niobium-doped ultra-high nickel ternary positive electrode material A2 was obtained.
[0047] S3: The positive electrode material A2 (20.53 mol) prepared in S2 and WO2 (0.4106 mol) were quickly mixed in a high-speed pulverizer, and then sintered for the second time in a tubular furnace under a 99% oxygen atmosphere at a high temperature of 750-770°C, a heating rate of 5°C / min, and a sintering time of 12h. After grinding with an agate mortar, sieving, and demagnetization, the ultra-high nickel ternary positive electrode material A3 doped with niobium and tungsten was obtained.
[0048] S4: ZIF-67 was prepared by room temperature synthesis: 1.192 g Co(NO3)2·6H2O was weighed on a balance, 100 mL methanol solution was measured with a measuring cylinder and poured into a 500 mL beaker X, the weighed Co(NO3)2·6H2O was poured into beaker X, and then ultrasonicated in an ultrasonic cleaner for 45 min to completely dissolve the Co(NO3)2·6H2O in the methanol solution; 1.312 g 2-methylimidazole was weighed on an analytical balance, 100 mL methanol was measured with a measuring cylinder and poured into a 500 mL beaker Y, the weighed 2-methylimidazole was poured into beaker Y, and then ultrasonicated in an ultrasonic cleaner for 45 min to completely dissolve the 2-methylimidazole in the methanol solution; the mixed solution in beaker X was poured into the mixed solution in beaker Y, covered with plastic wrap and allowed to stand at room temperature for 24 h; standing for 24 After h, a precipitate will form in the lower layer of the beaker. The upper clear liquid will be poured out, and the mixed solution with the precipitate in the lower layer will be placed in a centrifuge tube. Centrifuge at 10,000 r / min for 6 min, then pour out the upper clear liquid, and add methanol to continue centrifugation and washing twice. Finally, the washed precipitate is placed in a 120°C oven and dried for 24 h. The obtained white precipitate is ZIF-67 with high specific surface area and high crystallinity. ZIF-67 is sintered in a tubular furnace with a 99% nitrogen atmosphere at a sintering temperature of 490~500°C, a heating rate of 2°C / min, and a sintering time of 8h to obtain a ZIF-67 derivative. The ZIF-67 derivative (0.5133 mol) and A3 (20.53 mol) are placed in a ball mill for ball milling and mixing, and finally the ultra-high nickel ternary positive electrode material A4 coated with a niobium and tungsten composite doped ZIFs derivative is obtained. The electron microscope image is shown as follows: Figure 2As shown, it shows that the cathode material has successfully completed the doping of niobium and tungsten and the coating of ZIFs derivatives without affecting its sintering process.
[0049] Example 2
[0050] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0051] In step S1, the molar ratio of the mixed metal solution is 92:5:3; the concentration of the mixed metal solution is 105 g / L.
[0052] In step S2, the molar number of the niobium source is 0.3079 mol; the sintering temperature is 600-620° C.; and the sintering time is 16 h.
[0053] In step S3, the molar number of the tungsten source is 0.3079 mol; the sintering temperature is 720-740° C., and the sintering time is 14 h.
[0054] In step S4, the molar number of the ZIF-67 derivative is 0.6159 mol.
[0055] Example 3
[0056] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0057] In step S1, the molar ratio of the mixed metal solution is 90:3:7; the concentration of the mixed metal solution is 95 g / L.
[0058] In step S2, the molar number of the niobium source is 0.2053 mol; the sintering temperature is 630-650° C.; and the sintering time is 20 h.
[0059] In step S3, the molar number of the tungsten source is 0.3079 mol; the sintering temperature is 780-800° C., and the sintering time is 10 h.
[0060] In step S4, the molar number of the ZIF-67 derivative is 0.8212 mol.
[0061] Example 4
[0062] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0063] In step S1, the molar ratio of the mixed metal solution is 95:2:3; the concentration of the mixed metal solution is 105 g / L.
[0064] In step S2, the molar number of the niobium source is 0.6159 mol; the sintering temperature is 670-690° C.; and the sintering time is 15 h.
[0065] In step S3, the molar number of the tungsten source is 0.8212 mol; the sintering temperature is 710-730° C., and the sintering time is 13 h.
[0066] In step S4, the molar number of the ZIF-67 derivative is 0.5133 mol.
[0067] Example 5
[0068] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0069] In step S1, the molar ratio of the mixed metal solution is 95:2:3; the concentration of the mixed metal solution is 95 g / L.
[0070] In step S2, the molar number of the niobium source is 0.3079 mol; the sintering temperature is 700-720° C.; and the sintering time is 19 h.
[0071] In step S3, the molar number of the tungsten source is 0.5132 mol; the sintering temperature is 700-720° C., and the sintering time is 12 h.
[0072] In step S4, the molar number of the ZIF-67 derivative is 0.7185 mol.
[0073] Comparative Example 1 (Preparation of Ultra-High Nickel Ternary Positive Electrode Material without Doping and Coating)
[0074] S1: Nickel sulfate, cobalt sulfate and manganese sulfate are prepared into a 100g / L mixed metal solution in a molar ratio of 90:5:5, and then 8mol / L ammonia water and 10mol / L liquid alkali are placed in their corresponding storage tanks. First, the bottom liquid of the reactor is prepared. Under a nitrogen gas atmosphere, the ammonia pump is turned on to make the alkalinity of the pure water in the reactor reach 0.15~0.20mol / L, and then the liquid alkali pump is turned on to make the real pH (40℃) of the pure water in the reactor reach 11.95~12.05. After that, the seed crystal is started, and only the nickel-cobalt-manganese mixed solution feed pump is turned on, with a flow rate of 10~15ml / min, a feed amount of 50~60ml / min, and the real pH (40℃) is reduced to 10.9~11.0. Finally, the growth stage begins, and the coprecipitation reaction is started by the intermittent method. By controlling the flow rate of feed liquid, liquid alkali flow rate, ammonia flow rate, pH value, stirring blade speed, reaction temperature, reaction time and alkalinity, the particle size of the synthesized ultra-high nickel ternary precursor reaches 9~10μm. Finally, the synthesized ultra-high nickel ternary precursor is washed with water, washed with alkali, dried, sieved and demagnetized to obtain the ultra-high nickel ternary precursor E1 we need.
[0075] S2: The precursor E1 (20.53 mol) prepared in step 1 and LiOH (20.53 mol) were quickly mixed in a high-speed pulverizer, and then the first high-temperature sintering was carried out in a tubular furnace under 99% oxygen atmosphere. The sintering temperature was 650-670°C, the heating rate was 6°C / min, and the sintering time was 18h. Finally, the ultra-high nickel ternary positive electrode material E2 was obtained after grinding with an agate mortar, sieving, and demagnetization.
[0076] S3: The cathode material E2 (20.53 mol) prepared in step 2 was subjected to a second high-temperature sintering in a tubular furnace under 99% oxygen atmosphere, with a sintering temperature of 750-760°C, a heating rate of 5°C / min, and a sintering time of 12h. After grinding with an agate mortar, sieving, and demagnetization, the ultra-high nickel ternary cathode material E3 was obtained.
[0077] Comparative Example 2
[0078] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0079] In the first high temperature firing of S2, only LiOH is added without adding niobium source; in the second high temperature firing of S3, no tungsten source is added. In step S4, ZIFs derivative is added for coating, and the molar number of ZIF-67 derivative is 0.5133 mol.
[0080] Comparative Example 3
[0081] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0082] In step S2, the molar number of the niobium source is 0.6159 mol; the sintering temperature is 670-690°C; and the sintering time is 15 hours. No tungsten source is added in the second high-temperature sintering in S3, and then the ZIFs derivative is added in step S4 for coating.
[0083] Comparative Example 4
[0084] A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten is implemented by the method of Example 1, except that:
[0085] In the first high temperature sintering of S2, only LiOH is added without adding niobium source; in step S3, the molar number of tungsten source is 0.8212 mol; the sintering temperature is 710-730°C, and the sintering time is 13 hours. In step S4, ZIFs derivatives are added for coating.
[0086] Application Example 1
[0087] Battery assembly and performance testing: The prepared positive electrode material powder of the embodiment or comparative example, the conductive carbon black Super P and the binder polyvinylidene fluoride (PVDF) were manually and evenly ground in a mass ratio of 85:10:5. Add 0.5 g of 1-methyl-2-pyrrolidone (NMP) and stir evenly with a stirrer. The blades were coated using a flat coater, and the blade coating thickness was set to 0.02 mm (before drying). Dry at 80°C for 5 hours, then place in a vacuum oven at 100°C overnight. Cut out an electrode sheet with a diameter of 11.7 mm, put it in an argon box, and assemble the battery in sequence.
[0088] After assembly, the battery was aged for one day and then tested. The test method is: the battery was tested on a 5V-5mA or 5V-10mA blue battery test system. The test method is based on a current density of 1C=180 mA / g, and the charge and discharge experiment was carried out in the electrochemical window of 2.8 ~ 4.3V; and the charge and discharge cycle was completed at different rates of 0.5 C, 1 C, 2 C, 5 C, and 10 C. Table 1 shows the discharge specific capacity at different charge and discharge rates.
[0089] Table 1 Discharge capacity at different charge and discharge rates (mAh / g)
[0090]
[0091] Through Table 1 and Figure 3It can be seen that the doping of niobium and tungsten and the coating of ZIFs derivatives can significantly improve the rate performance of the positive electrode material; and the composite doping of niobium and tungsten and the coating of ZIFs derivatives have a synergistic effect, and both are indispensable.
[0092] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing an ultra-high nickel ternary positive electrode material coated with a ZIFs derivative doped with niobium and tungsten, characterized in that: The following steps are involved: L1. Grind and mix the ultra-high nickel ternary precursor and the niobium source evenly to obtain a mixture; L2, adding the mixed material to the lithium source and mixing them evenly in a high-speed pulverizer, and then firing them at a high temperature for the first time in a tubular furnace under an oxygen atmosphere, grinding the product with an agate mortar, and then sieving and demagnetizing the product in turn to obtain a niobium-doped ultra-high nickel ternary positive electrode material; L3, the niobium-doped ultra-high nickel ternary positive electrode material prepared in L2 is quickly mixed with a tungsten source in a high-speed pulverizer, and then fired for a second time at a high temperature in a tubular furnace under an oxygen atmosphere, and then sieved and demagnetized in turn after grinding with an agate mortar to obtain a niobium and tungsten composite-doped ultra-high nickel ternary positive electrode material; L4, preparing the ZIFs material by room temperature synthesis method, and then sintering it in a tubular furnace in a nitrogen atmosphere to obtain a ZIFs derivative; L5. Put the ZIFs derivative and the ultra-high nickel ternary positive electrode material doped with niobium and tungsten prepared in L3 into a ball mill for ball milling and mixing to obtain the ultra-high nickel ternary positive electrode material coated with the ZIFs derivative doped with niobium and tungsten.
2. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L1, the general formula of the ultra-high nickel ternary precursor is Ni x Co y Mn (1-x-y) (OH)2, where 0.9≤x<1, 0<y<0.1; The niobium source is at least one of Nb2O5, NbO2, Nb2O3, NbC and NbCl5, and the ratio of the molar number of niobium in the niobium source to the molar number of all metal elements in the ultra-high nickel ternary precursor is 1:(25~100).
3. The method for preparing the ultra-high nickel ternary positive electrode material coated with the niobium and tungsten composite doped ZIFs derivative according to claim 1, characterized in that: In L2, the lithium source is at least one of LiOH, Li2CO3 and Li2NO3, and the molar ratio of the ultra-high nickel ternary precursor to the lithium source is 1:(1.00~1.10).
4. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L2, the conditions for the first high-temperature firing are: continuous introduction of oxygen into the tubular furnace, sintering temperature of 600-900°C, sintering time of 12-20h, and heating rate of 2-12°C / min.
5. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L3, the tungsten source is WO2, WO3, Na2WO4·2H2O, WC and (NH4) 10 W 12 O 41 · at least one of 5H2O, the ratio of the molar number of tungsten in the tungsten source to the molar number of all elements in the ultra-high nickel ternary precursor is 1:(25~100).
6. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L3, the conditions for the second high-temperature firing are: continuous introduction of oxygen into the tubular furnace, sintering temperature of 500-800°C, sintering time of 10-16h, and heating rate of 2-12°C / min.
7. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L4, the ZIFs material is one of ZIF-8, ZIF-67, ZIF-11, ZIF-68, and ZIF-71.
8. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L4, the sintering conditions for preparing the ZIFs derivatives are: the sintering temperature in the tubular furnace is 500-700°C, the sintering time is 8-12h, and the heating rate is 2-12°C / min.
9. The method for preparing the ultra-high nickel ternary positive electrode material coated with the ZIFs derivatives doped with niobium and tungsten according to claim 1, characterized in that: In L5, the molar ratio of the ZIFs derivative to the ultra-high nickel ternary positive electrode material doped with niobium and tungsten prepared in L3 is 1:(25~100), and the ball milling speed is 200~800r / min.
10. Use of the niobium and tungsten composite doped ultra-high nickel ternary positive electrode material prepared by the method according to any one of claims 1 to 9 in lithium-ion batteries.